Youngblood [videorecording (DVD)] - Markle, Peter; Whitman, John (Aircraft Pictures, 2026)
Raised on grit and hockey by his hardline father, Dean Youngblood leaves Detroit to join Canada's Hamilton Mustangs. His elite skill turns heads, but his arrogance earns enemies and keeps him benched by a resentful coach. After a costly clash with rival goon Carl Racki, Dean finds guidance from team captain Sutton and unexpected love with the coach's daughter. When Racki brutally injures Sutton, Dean faces a defining playoff showdown and a choice between rage and maturity.